Preventive Vitamin A Supplementation Improves Striatal Function in 6-Hydroxydopamine Hemiparkinsonian Rats - Marie, Anaïs; Leroy, Julien; Darricau, Morgane; Alfos, Serge; De Smedt-Peyrusse, Veronique; Richard, Emmanuel; Vancassel, Sylvie; Bosch-Bouju, Clementine (Frontiers in Nutrition, 2022)
Background The mechanisms leading to a loss of dopaminergic (DA) neurons from the substantia nigra pars compacta (SNc) in Parkinson's disease (PD) have multifactorial origins. In this context, nutrition is currently investigated as a modifiable environmental factor for the prevention of PD. In particular, initial studies revealed the deleterious consequences of vitamin A signaling failure on dopamine-related motor behaviors. However, the potential of vitamin A supplementation itself to prevent neurodegeneration has not been established yet. Objective The hypothesis tested in this study is that preventive vitamin A supplementation can protect DA neurons in a rat model of PD. Methods The impact of a 5-week preventive supplementation with vitamin A (20 IU/g of diet) was measured on motor and neurobiological alterations induced by 6-hydroxydopamine (6-OHDA) unilateral injections in the striatum of rats. Rotarod, step test and cylinder tests were performed up to 3 weeks after the lesion. Post-mortem analyses (retinol and monoamines dosages, western blots, immunofluorescence) were performed to investigate neurobiological processes. Results Vitamin A supplementation improved voluntary movements in the cylinder test. In 6-OHDA lesioned rats, a marked decrease of dopamine levels in striatum homogenates was measured. Tyrosine hydroxylase labeling in the SNc and in the striatum was significantly decreased by 6-OHDA injection, without effect of vitamin A. By contrast, vitamin A supplementation increased striatal expression of D2 and RXR receptors in the striatum of 6-OHDA lesioned rats. Conclusions Vitamin A supplementation partially alleviates motor alterations and improved striatal function, revealing a possible beneficial preventive approach for PD.